Peran Pemerintah terhadap Kebersihan Lingkungan di Kelurahan Wawalintouan Kecamatan Tondano Barat Kabupaten Minahasa - Melpa Riama Hutapea; Theodorus Pangalila; Telly D. Wua (CV. Kurnia Grup, 2026)
Environmental hygiene issues in Wawalintouan Village, West Tondano District, are still an issue that needs serious attention. This is seen from the low level of community awareness in maintaining cleanliness, the waste management system that has not run optimally, as well as the limitations of supporting facilities provided by the government. This situation affects the decline in environmental quality and has the potential to disrupt public health. This study aims to determine the role of the government and community awareness of environmental hygiene. The research method used is a qualitative approach with a descriptive research type. Data collection was carried out through observation, interviews, and documentation techniques. Research informants consisted of village government officials and community members residing in the area. The results showed that the government had tried to carry out its role through socialization activities, provision of trash bins, and implementation of mutual cooperation with the community. However, these efforts have not been fully optimal because there are still limitations in facilities and infrastructure, as well as a low level of community participation. In addition, aspects of supervision and enforcement of rules still need to be strengthened.